Demand for international reserves: evidence from East Asia - Nor, Eliza; Mohamed, Azali; Law, Siong Hook (Inderscience Enterprises, 2009)
This paper examines the demand for international reserves in nine East Asian economies during the period 1970-2005 using panel cointegration and Fully Modified Ordinary Least Squares (FMOLS). The panel cointegration tests find the existence of a long-run relationship between the demand for international reserves and its determinants. The panel group FMOLS results indicate that current account balance and total external debt are statistically significant and exert a positive and negative impact, respectively, on the demand for international reserves in East Asia.